Pengaruh employee relation terhadap motivasi kerja karyawan di u pashaa seminyak - I Gusti Agung Ayu Nita Setianingsih; Agus Muriawan Putra; Putu Ratih Pertiwi (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2021)
As a hotel with an occupancy rate above 50% every year, U Paasha Seminyak in its operations certainly does not escape complaints. Based on recorded data, the number of complaints has increased in the past year. This indicates that the quality of employee performance has decreased, and employee discipline is still lacking in relation to absenteeism and working time so that management seeks to increase employee motivation to improve employee productivity and discipline through employee relations. The aims of this study was to determine the application of employee relations and their influence significantly on employee work motivation. Data collection techniques used were observation, interviews, questionnaires, literature study and documentation. The sampling technique uses proportional stratified sampling with a sample of 80 respondents. The data is processed using SPSS 24. Data analysis techniques are validity, reliability, simple regression analysis, and t-test with a significant level of 5 percent. Employee relations programs implemented to improve employee motivation include the Education and Training Program, the Award Program, Special Program Programs, the Employee Communication Program, the Profit Share, and the Employee Attitude Survey. Hypothesis test results state that the employee relations variable has a positive and significant effect on employee work motivation variables because a significance value of 0,000 <0.05 is obtained, a regression coefficient of 0.626 is positive and the t value is greater than t table 9.726> 1.991. Therefore the employee relations program needs to be implemented because it has succeeded in increasing the work motivation of employees at U Paasha Seminyak. Keywords :Employee Relation, Employee Motivation, Hotel